Chemistry of Carbon Nanostructures - Angelova, Polina; Bianco, Alberto; Eigler, Siegfried; Feng, Xinliang; Gölzhäuser, Armin; Hirsch, Andreas; Itami, Kenichiro; Krüger, Anke; Liu, Yunqi; Muellen, Klaus; Samori, Paolo; Segawa, Yasutomo; et al. (De Gruyter, 2017)
Chemistry of Carbon Nanostructures aims to present the current state-of-the-art synthesis and application of carbon materials like nano diamonds, ribbons and graphene-like structures in science and engineering. Edited by Professor Klaus Müllen, who received the Adolf von Bayer Medal for his contribution to Carbon Chemistry, and Xinliang Feng, this book combines outstanding contributions by a renowned international team of experts. The authors discuss chemical aspects of carbon nanostructures, their synthesis, functionalization and design strategies for defi ned applications. Recent advances in carbon nanomembranes, molecule-assisted ultrasound-induced liquid-phase exfoliation of graphene, and solution synthesis of graphene nanoribbons and biological application of nanodiamonds are highlighted topics. This book provides an excellent reference on the chemistry of carbon nanostructures for Chemists, Materials Scientists, Condensed-matter Physicists, Surface Scientists, and Engineers.